Diversity of speeches on play and education: Outlining the contemporary bulk of tendencies - Avanço, Leonardo Dias; de Lima, José Milton [UNESP] (FapUNIFESP (SciELO), 2020)
The main goal of this study was to find the relationships between play and education in contemporaneity. Specifically, the study aimed to outline a problem seen on the scope of speeches and practical experience. In that context, the study searched for conceptions of the relation between play and education that emerge from speeches and practices, thereby offering a systematic view of the situation that deserves attention and multiple approaches, since formative processes in various levels are to be improved. The methodology of this study was theoretical-bibliographic in nature. As results, the study provides an overview and appreciation of the bulk of current conceptions of the relation between play and education. In addition, the existence of a tension state is revealed in two senses: discrepancies of the value given to the role of play and the formative function of play are discussed; and complementarities and conflicts among conceptions are evidenced. The main result, however, is the conscience derived from the examination carried out in this study, which allows one to observe a hypothesis capable of explaining the reasons for the contrast and to offer theoretical solutions and accurate techniques for the formative fruitfulness of ludicity.
Keywords: Conception; Formative processes; Ludicity